English Teachers' Perceptions of Technological Pedagogical and Content Knowledge (TPACK) and Its Application in English Language Teaching: Post-COVID-19 - Indi Ramadhani Daulay; Rahmah Fithriani (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2024)
This study explores the evolving perceptions of English teachers regarding the integration of Technological Pedagogical Content Knowledge (TPACK) and its application in English Language Teaching (ELT) in the post-Covid-19 educational landscape. Insights drawn from educators' experiences in innovatively incorporating TPACK to increase student engagement, facilitate personalized learning experiences, and improve communication. This study highlights the influence of TPACK on pedagogical strategies in response to the dynamic post-pandemic educational landscape.